DETERMINAN TINGKAT KREDIT MACET BANK UMUM KONVENSIONAL PERIODE 2015-2019 - Thesya Yuzevin; Hanung Eka Atmaja; Heni Hirawati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of Return On Assets (ROA), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Costs of Operating Income (BOPO) and inflation rates on the level of non-performing loans (NPL) in commercial banks. conventional in Indonesia for the 2015-2019 period. This research is an explanatory research that uses multiple linear regression analysis techniques. The data analysis technique uses panel data regression with a population of 29 conventional commercial banks in Indonesia. The data of this study are secondary data obtained by documentation by the Indonesia Stocks Exchange. The results showed that the variables Return On Assets (ROA), Loan to Deposit Ratio (LDR), and the inflation rate had no effect on the level of Non Performing Loans (NPL). The variable Capital Adequacy Ratio (CAR) has a negative effect on Non-Performing Loans (NPL) with a coefficient of 0.034 at a significance level of 0.025 and the variable Operating Costs of Operating Income (BOPO) has a positive effect with a coefficient of 0.042 and a significance level of 0.046.